Exploring Students’ Perceptions of EFL Teachers’ TPACK Knowledge in Online Classroom Environment - Ma'rifatul Ilmi; Nur Arifah Drajati; Kristian Adi Putra (AL-ISHLAH: Jurnal Pendidikan, 2023)
Many studies have investigated students’ perceptions of experiencing technology-based English as Foreign Language (EFL) learning, particularly as a result of the Covid-19 Pandemic period. Only a few studies have considered the students’ perceptions of the teachers’ knowledge of integrating technology into the teaching and learning process. Thus, this study explored how students perceived their teacher’s knowledge of technology integration in teaching, especially in the case of technology pedagogy and content knowledge (TPACK) in the online classroom. A case study was applied in this study with five participants selected purposively. This study was mainly guided by six survey items validated by Chuang et al. (2018) about assessing teachers’ TPACK from the students’ perspectives. These six items were used as the guiding questions during the semi-structured interview. Further, this study also gathered data from the students’ responses or written reflections after class. Data were then analyzed thematically. The results indicated that these students perceived the teacher as having sufficient knowledge of teaching the subject matter. The TPACK knowledge, however, needed more attention to developing. It implied that educational policymakers, not limited to the institutional stakeholders and practitioners, should provide a TPACK-based professional development program to strengthen the teachers’ proficiency in technology-enhanced foreign language teaching.